2006
DOI: 10.1080/00324720500436011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of number of births on women's mortality: Systematic review of the evidence for women who have completed their childbearing

Abstract: Mortality in women who have completed their childbearing may increase with the number of births experienced because of maternal depletion or a trade-off between reproduction and mortality. We report a systematic review of the evidence on this association. We searched Medline, Embase, Popline, and the Science Citation Index for published and unpublished studies up to September 2003, and the book catalogues of relevant London libraries. Where necessary we also contacted authors for additional information. Mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 58 publications
10
145
2
3
Order By: Relevance
“…Since then, a freshly motivated field of investigators has reported mixed results in human populations, in some cases even showing a positive association between the number of offspring and longevity (reviewed by Helle et al 2005;Hurt et al 2006;Le Bourg 2007). This positive association may imply that successful reproduction, especially at advanced age, is a surrogate for increased fitness or quality of the mother (Doblhammer and Oeppen 2003;Gagnon et al 2009;Korpelainen 2000;McArdle et al 2006;Smith et al 2002;Yi and Vaupel 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a freshly motivated field of investigators has reported mixed results in human populations, in some cases even showing a positive association between the number of offspring and longevity (reviewed by Helle et al 2005;Hurt et al 2006;Le Bourg 2007). This positive association may imply that successful reproduction, especially at advanced age, is a surrogate for increased fitness or quality of the mother (Doblhammer and Oeppen 2003;Gagnon et al 2009;Korpelainen 2000;McArdle et al 2006;Smith et al 2002;Yi and Vaupel 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hurt et al [20] found that in some selected cases, mortality actually declined with increasing births among 12 historical cohorts (populations unable to benefit from better healthcare available in modern societies), though results were inconsistent and not always significant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one alternative explanation could be a selection effect regarding the respondent who entered SHARE. Respondents with high fertility may face greater risk of dying earlier (Hurt, Ronsmans and Thomas 2006;Bulled and Sosis 2010), and it could thus be that especially older respondents with fewer children entered SHARE. On the contrary, recent research suggests no consistent pattern in the association between mortality and number of births among women who have completed their childbearing (Hurt, Ronsmans and Thomas 2006).…”
Section: M4 Measuring Fertility In the Share Surveymentioning
confidence: 99%
“…Respondents with high fertility may face greater risk of dying earlier (Hurt, Ronsmans and Thomas 2006;Bulled and Sosis 2010), and it could thus be that especially older respondents with fewer children entered SHARE. On the contrary, recent research suggests no consistent pattern in the association between mortality and number of births among women who have completed their childbearing (Hurt, Ronsmans and Thomas 2006). Moreover, life expectancy seems to vary according to regional socio-economic contexts that also influence fertility (Bulled and Sosis 2010).…”
Section: M4 Measuring Fertility In the Share Surveymentioning
confidence: 99%